Economic pressure and political expression: understanding the dynamics of the boycott movement against Israeli products / Muhammad Azril Roslan and Ku Mohd Amir Aizat Ku Yusof - Roslan, Muhammad Azril; Ku Yusof, Ku Mohd Amir Aizat (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Boycotts' rights have long served as potent tools utilised by individuals and groups to protest perceived injustices or advocate for change. In recent years, the global boycott movement against Israeli products has gained substantial traction, sparking debates and controversies. This article aims to explore the nature of boycotts, their historical context, the ongoing Israel-Palestine conflict, and the impact and effectiveness of the boycott movement worldwide, with a particular focus on Malaysia. A boycott is a concerted effort by individuals, organisations, or nations to refrain from purchasing or using goods, services, or engaging with entities to express disapproval or effect change. Boycotts can address various issues including social injustice, labour practices, environmental concerns, and political conflicts. They operate on the principle of economic pressure, aiming to disrupt the financial interests of the target and compel them to alter their behaviour or policies.